Dual role of Lyz2-positive myeloid cells in traumatic brain injury: acute anti-inflammatory effects vs. chronic neurological deterioration - Yan, Hua-Zheng; Fang, Yi-Wan; Zhou, Shi-Yu; Gao, Jian-Xiong; Bian, Ming-Ming; Xu, Yao-Mei; Zhang, Lin; Zhang, Nan; Lü, He-Zuo (Frontiers in Cellular Neuroscience, 2025)
IntroductionNeuroinflammation is a critical factor contributing to secondary brain injury following traumatic brain injury (TBI). This process engages diverse cell types within the central nervous system (CNS), including significant infiltration of myeloid lineage cells–primarily neutrophils and macrophages–during the acute and subacute phases of TBI. These myeloid-derived cells represent a major population that critically influences the development and progression of neuroinflammation. Microglia and peripherally infiltrating macrophages exhibit polarization phenotypes that play a pivotal role in modulating inflammatory changes. Due to their functional and phenotypic similarities, their distinct contributions to the inflammatory response in TBI remain a subject of considerable debate. Lysozyme 2 (Lyz2) is a well-established marker for myeloid lineage cells (including monocytes, macrophages, and neutrophils) in mice, allowing specific targeting and depletion of these cells to dissect their functional roles in TBI.MethodsIn the present study, we investigated the trend of inflammatory factors during the early stage of TBI using Lyz2-IRES-DTREGFP transgenic mice, which specifically target and deplete Lyz2-positive myeloid cells. Tissue samples for RT-qPCR and flow cytometry were harvested from the perilesional cortex (within a 2-mm radius of the impact site) and the underlying hippocampus.Results and discussionOur findings revealed a considerable reduction in the expression of pro-inflammatory factors (e.g., IL-1β, iNOS, IL-6, IFN-γ) and an increase in the expression of anti-inflammatory factors (e.g., IL-4, IL-10, IL-13, Arg-1). Furthermore, we observed a shift in polarization phenotypes, characterized by a decreased proportion of M1 macrophages and an increased proportion of M2 macrophages. However, during the chronic phase, behavioral and histological analyses revealed worse outcomes. These findings demonstrate that targeted depletion of Lyz2-positive myeloid cells during acute TBI attenuates neuroinflammation. However, this early immunomodulatory shift correlates paradoxically with exacerbated chronic neurological deficits, suggesting that transient suppression of myeloid-driven inflammation may disrupt long-term reparative processes critical for functional recovery after TBI.